2001
DOI: 10.1073/pnas.211427898
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced changes in cerebral metabolites, hippocampal volume, and cell proliferation are prevented by antidepressant treatment with tianeptine

Abstract: Stress-induced structural remodeling in the adult hippocampus, involving debranching and shortening of dendrites and suppression of neurogenesis, provides a cellular basis for understanding the impairment of neural plasticity in the human hippocampus in depressive illness. Accordingly, reversal of structural remodeling may be a desirable goal for antidepressant therapy. The present study investigated the effect of tianeptine, a modified tricyclic antidepressant, in the chronic psychosocial stress model of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
615
2
11

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 968 publications
(675 citation statements)
references
References 65 publications
47
615
2
11
Order By: Relevance
“…The modified unbiased stereology protocol (Keuker et al, 2001) we used has been successful in quantifying BrdU labeling (Malberg et al, 2000;Czéh et al, 2001). Every sixth section throughout the dentate gyrus was examined, yielding a mean of 16 sections per animal.…”
Section: Quantification Of Brdu-labeled Cellsmentioning
confidence: 99%
“…The modified unbiased stereology protocol (Keuker et al, 2001) we used has been successful in quantifying BrdU labeling (Malberg et al, 2000;Czéh et al, 2001). Every sixth section throughout the dentate gyrus was examined, yielding a mean of 16 sections per animal.…”
Section: Quantification Of Brdu-labeled Cellsmentioning
confidence: 99%
“…On the contrary, the effect of antidepressant treatment on cytoskeletal and synaptic plasticity remains controversial. For instance, despite Czéh et al (2001) have shown that the atypical antidepressant tianeptine prevents the hippocampal volume loss induced by stress and Magariños et al (1999) have proved tianeptine efficacy to reverse stress-induced rat hippocampal atrophy visualized by Golgi staining, fluoxetine (FLX) has not been effective on these cytoskeletal changes (Magariños et al, 1999). In coincidence with these preclinical reports, clinical studies have not been able to confirm that antidepressant treatment reverses the hippocampal volume diminution found in depressed patients (Neumeister et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the antiapoptotic effect observed post-mortem by Lucassen et al, 85 tianeptine prevented the stressinduced reduction of the in vivo brain metabolite levels of N-acetylaspartate. 22 Several other studies have shown protective effects of antidepressants in different models, and mostly in the hippocampus. 58,86 In a maternal deprivation and a prenatal restraint stress model, alterations in granule cell number and neurogenesis as well as apoptosis occur 87,88 and these changes could be normalized by fluoxetine treatment.…”
Section: Cytoprotective Effectsmentioning
confidence: 97%
“…54 Tianeptine's effects of preventing or even, to some extent, reversing stress-induced structural plasticity have also been demonstrated in a more naturalistic psychosocial stress model. Czéh et al 22 have investigated whether administration of tianeptine would oppose stress-induced adverse effects in the hippocampal formation in the chronic psychosocial stress model of adult male tree shrews (Tupaia belangeri). This animal model has a high validity to investigate the pathophysiology of depressive disorders.…”
Section: Neurobiological Properties Of Tianeptinementioning
confidence: 99%
See 1 more Smart Citation